Isolation and Tentative Identification of Volatile Compound of Atung(Parinarium glaberrimum Hassk) Seed - Murhadi .; Soewarno T S.; Betty S.L Jennie.; Anton Apriyantono.; Sedarnawati Yasni (Jurnal Teknologi dan Industri Pangan, 2003)
The extraction of volatile components from “atung” seed was carried out by Likens Nickerson extraction apparatus with diethyl eter for 90 minutes, then continued with separation, while volatile isolates identification was done by GC-MS (Shimadzu Qp 5000). The data obtained indicated that volatile components of “atung” seed tentatively are as follow: aldehydes is the largest (34%), alkanes (17%), alkenes (11%), alcohols (7%), and ketones (6%). However, most aldehyde groups were predicted as derivative compounds resulted from the decomposition of fats and/or fatty acids due to a high temperature extraction process. Key words : Volatile components, “atung” seeds, Likens Nickerson, GC-MS, aldehydes.